Differences in Mental Health Based on Age and Gender of the Elderly in Social Shelters - Farsida Farsida; Syahrizal Mahara; Umi Sjarqiah; Tri Ariguntar Wikanningtyas; Rahmini Shabariah (Indonesian Journal of Global Health Research, 2025)
Mental health in older adults is shaped by physical and social environments, life experiences, and aging-related challenges like declining capacity, reduced functionality, and psychological stress. The 2019 Global Health Estimates (GHE) reports mental disorders account for 10.6% of elderly disability, with 14% of those aged 60 and over affected, primarily by depression and anxiety. Objective: This study aims to examine the differences in mental health based on age and gender among the elderly in social shelters. Methods: A cross-sectional study was conducted at the social shelter, in September-October 2023. A sample of 80 elderly individuals was selected using purposive sampling. Data were collected through interviews using a questionnaire with the DASS 21 (Depression Anxiety Stress Scales) instrument. Data analysis was performed using chi-square tests. Results: Most had normal mental health: depression (43.8%), anxiety (61.2%), and stress (76.2%). Gender correlated with anxiety (p<0.001) but not depression or stress, while age showed no significant relationships. Conclusion: Most elderly in the shelter had normal mental health, with gender linked to anxiety and age unrelated to depression, anxiety, or stress. These findings emphasize the importance of considering gender factors in efforts to improve mental health among the elderly.